Intestinal Continuity Alleviates Pediatric Intestinal Failure-Associated Liver Disease - Wang, Jinling; Yan, Weihui; Lu, Lina; Tao, Yijing; Huang, Liufang; Cai, Wei; Wang, Ying (Frontiers in Surgery, 2022)
Background: When ileostomy or jejunostomy are performed after resecting the intestine for necrotizing enterocolitis (NEC) or intestinal atresia, it is called type I short bowel syndrome (SBS). This condition requires long-term parenteral nutrition (PN) and is often accompanied with intestinal failure-associated liver disease (IFALD). This study aimed to observe the impact of intestinal continuity on the hepatic function of pediatric intestinal failure (IF) patients with type I SBS. Methods: The pre-and post-anastomosis medical records of 35 pediatric patients with type I SBS were reviewed retrospectively from April 2013 to April 2019. The average growth (cm/month) in the proximal and distal intestinal lengths was calculated as the growth in intestinal length (cm)/the duration (month) from enterostomy to anastomosis. Hepatic function was assessed before anastomosis for 6 weeks and after anastomosis for 4 weeks to evaluate the changes in hepatic function from enterostomy to anastomosis. Results: The average growth in proximal intestinal length was 9.3 cm/month (±7.2) in neonates and 2.8 cm/month (1.3, 11.9) in infants and children, and in distal intestinal length was 1.5 cm/month (0, 2.7) in neonates and 0.4 cm/month (0, 1.4) in infants and children. The incidence of IFALD was 28.6% 1 month before anastomosis and 20.0% 1 month after anastomosis (P <0.05). Conclusion: In pediatric type I SBS with IFALD, restoration of intestinal continuity may alleviate liver injury. There was an intestinal compensatory effect on the growth in the intestinal length after resection, and better results were seen in neonates in terms of intestinal length growth.